2008
DOI: 10.1017/s0950268808000654
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR for differential diagnosis of emerging typhoidal pathogens directly from blood samples

Abstract: Classically Salmonella enterica serovar Typhi (S. Typhi) is associated with typhoid, a major health problem in developing countries. However, in recent years S. Paratyphi A and Vi-negative variants of S. Typhi have emerged rapidly. We have developed a nested multiplex PCR targeting five different genes for differential diagnosis of typhoidal pathogens which has been optimized to be directly applicable on clinical blood samples. Of 42 multiplex PCR-positive blood samples, 26, nine, and two were Vi-positive S. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…TH and AH [22]. The other study, based on nucleic acid amplification from blood samples of enteric fever patient's has also shown 12% positivity for both the serotypes [11]. Interestingly, 16.4% of the blood samples in the present study were also found positive for the mixed infection.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…TH and AH [22]. The other study, based on nucleic acid amplification from blood samples of enteric fever patient's has also shown 12% positivity for both the serotypes [11]. Interestingly, 16.4% of the blood samples in the present study were also found positive for the mixed infection.…”
Section: Discussionsupporting
confidence: 60%
“…The possibility of co-infection has already been suggested by the population based serological study from Nigeria [4] and nucleic acid based detection in blood from Pakistan in acute enteric fever cases [11]. Moreover, S. ParaTyphi A causes indistinguishable clinical features [8] and may be associated with more complications [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These results show that the nested PCR has good potential to be a rapid tool for the definitive, differential diagnosis of typhoid and is superior to conventional methods 57 .…”
Section: Pcrmentioning
confidence: 82%
“…During analysis of 60 stored strains of serovar Typhi from the Faisalabad region of Pakistan by PCR for the presence of SPI-7 and two genes essential for Vi production: tviA and tviB, 9 (15%) were tested negative for both tviA and tviB, while only two of such strains lacked SPI-7 [3]. Furthermore, the 42 multiplex PCR-positive isolates from the Faisalabad region of Pakistan included 9 Vi negatives [4].…”
mentioning
confidence: 99%
“…The expanded usage of conjugated Vi vaccines [1] in areas with frequent circulation of Vi-negative isolates [3,4] could aid in selection and dissemination of the Vi-negative strains in the community. The role of circulating Vi-negative strains could be tremendous following extended usage of Vi vaccines.…”
mentioning
confidence: 99%